PENGARUH PROFITABILITAS DAN HUTANG TERHADAP PEMBAYARAN DIVIDEN TUNAI PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Muhammad Ridha Ramli (SI-MEN, 2015)
This study aims to determine the effect of profitability and debt to cash dividend payments,either individually (partial) or together (simultaneously). This study uses census andperformed on a mining company listed on the Indonesia Stock Exchange that have met thepopulation criteria. Research data observation period from 2008 till 2011, whichamounted to 14 mining companies that have met the criteria. The analytical method used ismultiple linear regression. Results of this study found an effect on the profitability and debtpayments of cash dividends, either individually (partial) or together (simultaneously).